Majlis Bandaraya Ipoh / Nurul Nabila Azman - Azman, Nurul Nabila (Universiti Teknologi MARA, Perlis, 2023)
This internship report is based on a six-month internship programme that I successfully completed in Majlis Bandaraya Ipoh (MBI) from 1 March 2023 to 15 August 2023 as part of my Bachelor of Business Administration (Hons.) Finance at UiTM Campus Arau, Perlis. As an individual who was absolutely new to the practical, business-oriented context, every hour spent in the Treasury Department provided me with valuable experience that cannot be expressed in words. Nonetheless, they were all beneficial to my profession. This report comprises how the Majlis Bandaraya Ipoh or to be specific Treasury Department works. Basically, I did my internship at three different units, which are the Expense and Salary unit, the Parking unit, and the Tax unit. At each unit, I gained a lot of knowledge and experience. In addition, Majlis Bandaraya Ipoh have many wings which are Unit Jabatan Teknologi Maklumat, Unit Pesuruhjaya Bangunan, Unit Audit Dalam, Unit Perundangan, Unit Korporat dan Aduan Awam, Unit Pusat Setempat, Unit Pentadbiran UTC Perak, and many more.